How Does AI Support Tumor Board Decision Making? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Multidisciplinary tumor boards (MDTs) are the cornerstone of modern cancer care, bringing together a diverse team of specialists, including oncologists, surg...
Keywords: AI in Oncology; Support; Tumor; Board; Artificial Intelligence; Machine Learning; Deep Learning